EVALUASI PELAKSANAAN PROGRAM MOBIL PUSAT LAYANAN INTERNET KECAMATAN (M-PLIK) DI KOTA PEKANBARU TAHUN 2012-2013 - Putra, Yogi Dwi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Internet Service Center Subdistrict (PLIK) and Mobile Internet Service Center Subdistrict (MPLIK) is a program of the Ministry of Communication and Information of the Republic of Indonesia (Kemkominfo RI), with the aim of supporting the expansion of Internet access services for the wider community and as the acceleration of the increase in affordability of equity of services and utilization for the purpose increase intelligence and social welfare, especially in the districts. Car internet service provider districts is the mandate of the Regulation of the Minister of Communication and Information No.19 / PER / M.KOMINFO / 12/2010. The problem in this research, MPLIK not operate properly according to Standard, lack of coordination and the seriousness of the manager / managing partner in the operation MPLIK and more often to settle because of limited operational funds, distribution MPLIK has not been done according to the target, coordination and dissemination program MPLIK with Local Government relatively minimal, Based on this background, authors are encouraged to do research with the title "Car Program Implementation Evaluation District Internet Service Center (M-PLIK) in the city of Pekanbaru Year 2012-2013" .Teori (approach) that I use as a tool of analysis in this study is a theory of evaluation and implementation. While the methods used in this study is a qualitative method, which seeks to analyze the evaluation and provide an explanation of data obtained from observations and aim to reinforce and strengthen a theory so as to obtain information about the current situation. Data collection techniques in this research is to use interview techniques and documentation.It can be concluded, in this study Effectiveness program MPLIK still clearly visible, Efficiency MPLIK in terms of the Fund obtained was unclear due to the unclear responsibility of the party who has been appointed the managing, resposibility Car Program Service Center District Internet (MPLIK) in Pekanbaru there are some areas that do not need or in mapping the area that is not appropriate, the aspect Accuracy Car Program District Internet Service Center (MPLIK) in the city of Pekanbaru is not in accordance with the Regulation of the Minister of Communication and Information 1 Year 2013 on the Provision of Internet access Services in the Service area universal Telecommunication District of Article 4, paragraph 1, which reads each PLIK must connect with SIMMLIK managed and operated by BP3TI.Keywords:Evaluation,Implementation, Mobile Internet Service Center Subdistrict